The Role of Social Entrepreneurship in Empowering Local Governance: A Study of Kalikot District, Karnali Region, Nepal - Neupane, Gokul Prasad; Baral, Navaraj (Journal of Multidisciplinary Research Advancements, 2026)
This study seeks to establish the link between social entrepreneurship and local governance in Kalikot district, Karnali Region, Nepal. It aims to identify how socially inspired and innovative approaches to business can help address some of the drawbacks of conventional governance systems and contribute to good governance ideals such as accountability, transparency, participation, and efficiency. A descriptive and causal-comparative study was conducted using survey data collected from 396 respondents in Kalikot district. The study established a strong positive correlation among social entrepreneurship, its perceived characteristics, prevalence, support from municipal governments, and its relevance relative to conventional approaches and good governance. The results from regression analysis confirm that all these factors are significant determinants of governance outcomes. The study concludes that, though local governments are still developing and consolidating within the federal structure, social entrepreneurship is a viable alternative route to promote sustainable socio-economic development and governance in the Karnali Region.